2012
DOI: 10.1007/s11357-012-9391-0
|View full text |Cite
|
Sign up to set email alerts
|

Exceptionally old mice are highly resistant to lipoxidation-derived molecular damage

Abstract: Membrane unsaturation plays an important role in the aging process and the determination of inter-species animal longevity. Furthermore, the accumulation of oxidation-derived molecular damage to cellular components particularly in the nervous and immune systems over time leads to homeostasis loss, which highly influences age-related morbidity and mortality. In this context, it is of great interest to know and discern the degree of membrane unsaturation and the steady-state levels of oxidative damage in both ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…Oxidative damage of critical biological molecules resulted from alteration in a cellular redox state and accumulation of reactive oxygen species (ROS) is considered one of the causal factors of aging [ 56 58 ]. Our study revealed considerable upregulation of genes associated with ROS production (Cyba), antioxidant defence system (Gpx6), regulation of redox state (Txnip), and membrane lipid sensitivity to oxidation (Scd2) in the old striatum, which is consistent with previous findings [ 29 , 59 62 ]. The Cyba or p22phox gene encodes the α -subunit of the membrane-associated NAD(P)H which is the second most important intracellular source of ROS after mitochondria [ 63 ].…”
Section: Discussionsupporting
confidence: 93%
“…Oxidative damage of critical biological molecules resulted from alteration in a cellular redox state and accumulation of reactive oxygen species (ROS) is considered one of the causal factors of aging [ 56 58 ]. Our study revealed considerable upregulation of genes associated with ROS production (Cyba), antioxidant defence system (Gpx6), regulation of redox state (Txnip), and membrane lipid sensitivity to oxidation (Scd2) in the old striatum, which is consistent with previous findings [ 29 , 59 62 ]. The Cyba or p22phox gene encodes the α -subunit of the membrane-associated NAD(P)H which is the second most important intracellular source of ROS after mitochondria [ 63 ].…”
Section: Discussionsupporting
confidence: 93%
“…This feature has also been observed during physiological aging since the efficiency of fat oxidation decreases with age in humans (31). Another possible explanation for the reduced MUFA/PUFA ratio is an increase in desaturating activities responsible for PUFA biosynthesis, which have also been associated to aging (32). Moreover, in agreement with our results several studies have shown that organs from different species present a membrane lipid profile with increased PUFAs as a result of aging (33) and a decrease in the number of unsaturations of long chain FFAs has been detected in plasma samples from long lived animals (34) The stearoyl-CoA desaturase-1 (SCD1) is a key enzyme in lipid metabolism since it synthesizes MUFAs, the building blocks of more complex lipids such as triacylglicerides, diacylglycerides, phospholipids and cholesterol esters.…”
Section: Discussionmentioning
confidence: 55%
“…In both comparisons, the PI of the mouse strain displaying extended longevity was significantly lower that than of the short-lived strain [ 73 , 85 , 103 ]. Identical results were obtained when membrane unsaturation and PI was evaluated in exceptionally long-lived specimens of mice [ 95 ]. Additionally, the comparison between closely-related species with divergent longevity, such as the long-lived white-footed mouse P. leucopus and the short-lived M. musculus, also displayed a lower PI for the long-lived mouse when compared to the common laboratory mouse [ 97 ].…”
Section: Membrane Unsaturation and Longevitymentioning
confidence: 55%